Efektifitas Konseling Berbasis Penyembuhan Spiritual Untuk Mereduksi Kecemasan Ibu Hamil Pada Trimester Ketiga - Muhtasor Muhtasor; Edy Irawan (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACTThe problem of psychological changes that cause discomfort, is generally experienced by pregnant women. These changes begin from the age of the first trimester to the third trimester, especially with psychological responses that can change at any time. This study aims to determine the effectiveness of spiritual counseling to reduce anxiety in the first third trimester of pregnant women. Testing the effectiveness of the model using the experimental method and the chosen design is the pretest and posttest control group design. The instrument used is the adoption anxiety measurement scale from Spielberger's (1979) theory. Based on hypothesis testing using analysis of covariance (ANACOVA) by controlling the nature of anxiety, it is known that there is an effect of counseling based on spiritual healing on reducing anxiety in pregnant women.Keywords: anxiety, spiritual counseling, third trimester pregnant women.ABSTRAKMasalah perubahan psikologis yang mengakibatkan ketidaknyamana, secara umum dialami oleh ibu hamil. Perubahan-perubahan tersebut diawali sejak usia trimester pertama hingga trimester ketiga terutama dengan respon psikologis yang dapat berubah-ubah setiap saat. Penelitian ini bertujuan mengetahui efektifitas konseling spiritual untuk mereduksi kecemasan pada ibu hamil pertama trimester ketiga. Pengujian efektivitas model menggunakan metode eksperimen dan desain yang dipilih adalah pretest and posttest control group design. Instrumen yang digunakan adalah skala pengukuran kecemasan adopsi dari teori Spielberger (1979). Berdasarkan pengujian hipotesis menggunakan analisis kovarian (ANAKOVA) dengan mengontrol sifat kecemasan, diketahui bahwa terdapat pengaruh konseling berbasis penyembuhan spiritual terhadap penurunan kecemasan ibu hamil.Kata Kunci : kecemasan, konseling spiritual, ibu hamil trimester ketiga.ABSTRACT The problem of psychological changes that cause discomfort, is generally experienced by pregnant women. These changes begin from the age of the first trimester to the third trimester, especially with psychological responses that can change at any time. This study aims to determine the effectiveness of spiritual counseling to reduce anxiety in the first third trimester of pregnant women. Testing the effectiveness of the model using the experimental method and the chosen design is the pretest and posttest control group design. The instrument used is the adoption anxiety measurement scale from Spielberger's (1979) theory. Based on hypothesis testing using analysis of covariance (ANACOVA) by controlling the nature of anxiety, it is known that there is an effect of counseling based on spiritual healing on reducing anxiety in pregnant women. Keywords:Anxiety, Spiritual Counseling, Third Trimester Pregnant Women  ABSTRAK Masalah perubahan psikologis yang mengakibatkan ketidaknyamana, secara umum dialami oleh ibu hamil. Perubahan-perubahan tersebut diawali sejak usia trimester pertama hingga trimester ketiga terutama dengan respon psikologis yang dapat berubah-ubah setiap saat.Penelitian ini bertujuan mengetahui efektifitas konseling spiritual untuk mereduksi kecemasan pada ibu hamil pertama trimester ketiga. Pengujian efektivitas model menggunakan metode eksperimen dan  desain yang dipilih adalah pretest and posttest control group design. Instrumen yang digunakan adalah skala pengukuran kecemasan adopsi dari teori Spielberger (1979). Berdasarkan pengujian hipotesis menggunakan analisis kovarian (ANAKOVA) dengan mengontrol sifat kecemasan, diketahui bahwa terdapat pengaruh konseling berbasis penyembuhan spiritual terhadap penurunan kecemasan ibu hamil.  Kata Kunci: Kecemasan, Konseling Spiritual, Ibu Hamil Trimester Ketiga